Discord-entanglement interplay in the thermodynamic limit: the xy-model - Batle, J. (2013)
We investigate thermal properties of quantum correlations in the thermodynamic limit with reference to the XY-model and the finite two-qubit Heisenberg model. Although this model has been the subject of active entanglement-research, the bulk of the pertinent work refers to finite instantiations. As a consequence, the temperature cannot be properly defined in such circumstances, a problem that is overcome here. Our effort should be of interest because quantum discord notion.